THE INFLUENCE OF MOTHER-CHILD ATTACHMENT AND CAREGIVER-CHILD INTERACTION ON PRESCHOOL CHILDREN’S SOCIAL-EMOTIONAL DEVELOPMENT - Alifah Nur Izzati; Neti Hernawati; Islamiah, Nur (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
In dual-earner families, the mother's role in fostering social-emotional development in children must be complemented by support from other caregivers, such as daycare staff. This study examines the impact of child and family characteristics, mother-child attachment, and caregiver-child interactions on the social-emotional development of preschool children attending daycare. Utilizing a quantitative approach with a cross-sectional design, the research was conducted in a daycare facility located in Bogor and included 40 mothers and their children, along with 20 caregivers. The findings revealed a significant positive relationship between mother-child attachment and children’s social-emotional development. Conversely, negative interactions between caregivers and children—particularly those characterized by harassment and detachment—were found to have a significant detrimental effect on children’s social-emotional development. Additionally, the analysis indicated that a secure mother-child attachment positively influences children’s social-emotional development, while negative interactions, such as harassment, detachment, and permissiveness among caregivers, adversely affect this aspect of development.